Controlled nano-particle dyeing of cotton can ensure low cytotoxicity risk with multi-functional property enhancement. (September 2020) - Khandual, A.; Rout, N.; Verma, S.K.; Patel, P.; Pattanaik, P.; Luximon, Y.; Kumar, A.; Nayak, R.K.; Suar, M.
Abstract: The Nanoparticle (NP) and their oxides are being progressively used and expected to be more frequently used in textiles. Nanoparticle (NP) has higher toxicological risk than larger particles because of their physicochemical properties, chemical reactivity and biological activity. In fact, the stability of nano-oxide particles in the medium is always challenging as they lack functional groups to leverage upon textile materials directly. Thus, in many finishing processes, cross-linkers and/or adhesives are applied together with NP at the cost of inferior comfort, feel and fastness which tends to be toxic and prone to release NPs under common laundering, physical stress and sweat. This study shows that the diffusion of NPs into the fibre polymer matrix via dyeing technique could be much durable, safer in terms of cytotoxicity levels and easy to process for tailoring desired functional attributes. We studied the possibility of a simple application technique via dyeing of vinyl sulphone based reactive dye with four kinds of NPs followed by their cytotoxicity test using cell line A431.1% silica dyed sample have shown highest (198.5%) increase in tensile strength followed by 2% silica and 2% CNT whereas a decrease in elongation is highest in the case of CNT 2% (5.31%) and significantly enhancing the moisture management properties in case of CNT and silica. The study showed promising results in dyeing with TiO2, CNT (Carbon nanotubes), Silica and Alumina NPs in enhancing the mechanical, moisture management, and surface frictional properties to ensure comfortable and safe wear. Graphical abstract: Image 1 Highlights: Commercial Nano-engineered functional textile prepared by coating, spinning or sol-gel methods show toxicological risk. The diffusion of NPs into the fiber polymer matrix via dyeing technique was defined for less cytotoxicity, and durability. TiO2, Carbon, Alumina and Silica NPs were incorporated via dyeing of vinylsulphone based reactive dye for enhanced mechanical and moisture management properties. NP-Dyed cotton textiles were less cytotoxic to A431 cell lines (epithelial cell lines).